Pengaruh Penggunaan Media Audiovisual Terhadap Hasil Belajar Matematika Siswa Pada Suplemen Pembelajaran Melalui Daring - Sazali, Nur Safira; Arjudin, Arjudin; Kurniawan, Eka; Sarjana, Ketut (Mandalika Mathematics and Educations Journal, 2024)
This study aims to determine the effect of the use of audiovisual media on students’ mathematics learning outcomes in the online learning supplement. This type of research is experimental research. The population in this study were class VIII students, with a sample determined using random sampling techniques. The samples in this research consists of 76 students, with class VIII-A as the experimental group and class VIII-B as the control group. The instrument used is a test of student learning outcomes. The data analysis used is the normality test and homogeneity test as a prerequisite test, the t test as a hypothesis test, and an effect size to determine whether there is an influence from the use of audiovisual media on student learning outcomes. According to the results of hypothesis testing using the t test at a 5% significance level, it was found that  and , indicating that  so the  is rejected  and the  is accepted. The effect size results showed a value of 0,804 which falls into the high category, meaning that there is an impact of using audiovisual media on students’ mathematics learning outcomes in the online learning supplement.